2021
DOI: 10.3389/fncir.2021.710925
|View full text |Cite
|
Sign up to set email alerts
|

Crossed Connections From Insular Cortex to the Contralateral Thalamus

Abstract: Sensory information in all modalities, except olfaction, is processed at the level of the thalamus before subsequent transmission to the cerebral cortex. This incoming sensory stream is refined and modulated in the thalamus by numerous descending corticothalamic projections originating in layer 6 that ultimately alter the sensitivity and selectivity for sensory features. In general, these sensory thalamo-cortico-thalamic loops are considered strictly unilateral, i.e., no contralateral crosstalk between cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…For instance, whole-brain tractography within a single animal is relative easy to acquire. Thus, these data can be used to examine contralateral thalamic connections, which have received less attention in macaque tracer studies (20,81,82).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, whole-brain tractography within a single animal is relative easy to acquire. Thus, these data can be used to examine contralateral thalamic connections, which have received less attention in macaque tracer studies (20,81,82).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, whole-brain tractography within a single animal is relative easy to acquire. Thus, these data can be used to examine contralateral thalamic connections, which have received less attention in macaque tracer studies (20, 81, 82). Our study shows that cortical parcels with diffuse ipsilateral thalamic connections also have diffuse bilateral thalamic connections, but this relationship wasn’t as strong for contralateral connections.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical layer 5 plays an important role for the transfer of sensory information from primary cortical areas to non-primary thalamic nuclei, which conveys information further to higher sensory cortical regions [ 42 , 43 , 47 , 109 , 110 ]. These layer 5 projections serve as feedforward projections that drive information between cortical areas via an alternate route of information flow, i.e., the cortico-thalamo-cortical route in addition to the traditional direct corticocortical pathway from upper cortical layers 2 and 3 [ 41 , 42 , 47 , 48 , 49 , 89 , 111 , 112 ]. In addition, these corticothalamic neurons in layer 5 send projections to motor centers, thereby affecting generated motor behaviors [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the ectopic cortical migration patterns observed in humans with ASD [ 45 , 46 ]. These ectopic projections might result in altered information flow through the cortico-thalamo-cortical pathway that might be involved in sensorimotor function impairment and the emergence of autistic behaviors [ 47 , 48 , 49 ]. Hence, exploring these corticothalamic circuit alterations will provide an understanding of aberrant neuroanatomical connections and mechanisms underlying the emergence of autistic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the differences between the EO and EC conditions, the FM group exhibited an increased lagged coherence connection between the left and right insula and between the left insula and right DLPFC in the beta-3 band (see Figure 2B ). Neuroimaging studies of experimentally induced acute pain have shown that the insula is a key structure for integrating sensory information with brain regions involved in cognitive, emotional, and executive functions ( Bastuji et al, 2016 ; Adeyelu et al, 2021 ; Wang et al, 2022 ). However, the functions of the insula extend beyond pain processing because they are associated with unpleasant interoceptive and exteroceptive experiences ( Craig, 2002 ).…”
Section: Discussionmentioning
confidence: 99%